Disillusionment and hope with transnational mothers: Avenues of change in education through acompañamiento. - Contreras, Ana (Anthropology & Education Quarterly, 2024)
This critical ethnographic study explores a participatory action research group consisting of Latin American immigrant mothers seeking to involve their community in school decision‐making. Drawing from pedagogies of acompañamiento, I describe how the mothers responded to decision‐making challenges and leveraged reflections on their struggles to co‐create knowledge and belonging. I demonstrate how their collective learning highlights transformation outside of formal policy channels, pushing us to consider alternative ways of making social change.